Pengaruh E-booklet Kearifan Lokal Sumatera Barat Terhadap Hasil Belajar Peserta Didik MAN 3 Padang: Penelitian - Arvy Anggara; Muhyiatul Fadhilah; Fitri Arsih; Rahmadhani Fitri; Edrawati; Wiwid Mardas (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
The purpose of this research is to examine the impact of an e-booklet infused with the local wisdom of West Sumatra on the learning outcomes of students at MAN 3 Padang. Currently, the learning outcomes of students at MAN 3 Padang are still considered low. This study uses an experimental method with a quasi-experimental design. The research population includes all students in class X Phase E at MAN 3 Padang, with a sample consisting of classes X E1 and X E3. Data was collected through multiple-choice tests given in the form of a posttest at the end of the research. Data analysis was conducted using normality tests, homogeneity tests, and hypothesis testing with the assistance of SPSS 20 software. The research results indicate that the learning outcomes of students in the experimental class is higher than that of the control class. Hypothesis testing shows a significance value of 2-tailed < 0.05, which is 0.030. Therefore, it can be concluded that the use of e-booklets with the nuances of local wisdom from West Sumatra has a positive impact on the learning outcomes of Phase E students at MAN 3 Padang.